Metabolic disturbances and worsening of atherosclerotic lesions in ApoE-/- mice after cola beverages drinking. - Otero-Losada, Matilde Estela (2013)
Atherosclerosis is a major health burden. Metabolic disorders had been associated with large consumption of soft drinks. The rising incidence of atherosclerosis and metabolic alterations warrants the study of long-term soft drink consumption´ effects on metabolism and atherosclerosis in genetic deficiency of apolipoprotein E which typically develops spontaneous atherosclerosis and metabolic alterations.